Comparison of curative effect between OBS assisted by 3D printing and PFNA in the treatment of AO/OTA type 31-A3 femoral intertrochanteric fractures in elderly patients - Huang, Jiazheng; Xiong, Ying; Mithu, Md Miftahul; Li, Jinping; Geng, Chengkui; Lu, Jipeng; Ren, Yunfeng; Yang, Ze; Gan, Xuewen; Zhang, Aili; Yang, Huiqin; Chen, Zhuoyuan (Frontiers in Medicine, 2023)
Objective: To compare and analyze the Ortho-Bridge System (OBS) clinical efficacy assisted by 3D printing and proximal femoral nail anti-rotation (PFNA) of AO/OTA type 31-A3 femoral intertrochanteric fractures in elderly patients. Methods: A retrospective analysis of 25 elderly patients diagnosed with AO/OTA type 31-A3 femoral intertrochanteric fracture was conducted from January 2020 to August 2022 at Yan’an Hospital, affiliated to Kunming Medical University. The patients were divided into 10 patients in the OBS group and 15 in the PFNA group according to different surgical methods. The OBS group reconstructed the bone models and designed the guide plate by computer before the operation, imported the data of the guide plate and bone models into a stereolithography apparatus (SLA) 3D printer, and printed them using photosensitive resin, thus obtaining the physical object, then simulating the operation and finally applying the guide plate to assist OBS to complete the operation; the PFNA group was treated by proximal femoral nail anti-rotation. The operation time, the intraoperative blood loss, Harris hip score (HHS), Oxford Hip Score (OHS), and complications were compared between the two groups. Results: The operation time and the intraoperative blood loss in the PFNA group were less than that in the OBS group, and there was a significant difference between the two groups (P<0.05). The HHS during the 6th month using OBS was statistically higher than PFNA (P<0.05), however, there were no significant differences in OHS during the 6th month between the OBS group and PFNA group (P>0.05). The HHS and OHS during the 12th month in the OBS group were statistically better than in the PFNA group (P<0.05). Conclusion: The OBS assisted by 3D printing and PFNA are eﬀective measures for treating intertrochanteric fractures. Prior to making any decisions regarding internal fixation, it is crucial to evaluate the distinct circumstances of each patient thoroughly.